Morphoagronomic performance of Cenchrus purpureus new clones - Fortes, Dayleni; Herrera, R. S.; Herrera, Magaly (Cuban Journal of Agricultural Science, 2023)
A random block design with four replications was used to study morphologic indicators and yield and the height relations with the regrowth age of Cenchrus purpureus new clones obtained in the Instituto de Ciencia Animal with promising characteristics for grazing. A total of five clones of Cenchrus purpureus were evaluated: CT-3, CT-7, CT-11, CT-26, CT-27and were compared with their progenitor C. purpureus vc. Cuba CT-115.In the rainy season the clones showed variable performance in the length and wide of leaves, in the first year the CT-3 showed the highest wide of leaves (2.50 cm) while in the second year there were not differences. The number of leaves/plant in the dry season was higher in the clones CT-3 and CT-26 (17 and 14.7 leaves/plant, respectively) in the first year, while in the second year was higher in CT-3, CT-26 and CT-27. Lineals, quadratic and cubic models were fitted for relate the plant height with the age and the yield with the age, with high coefficients of determination and signification. It was concluded that the most highlighted clones in the evaluated indicators, mainly in the dry season, were CT-3, CT-26 and CT-27. It is recommended to evaluate these clones under grazing conditions and got into the performance of its nutritive value. Key words: evaluation, Cenchrus, morphology, grazing